The Interaction Between Physical and Psychosocial Stressors - Abdelall, Esraa S.; Eagle, Zoe; Finseth, Tor; Mumani, Ahmad A.; Wang, Zhonglun; Dorneich, Michael C.; Stone, Richard T. (Frontiers in Behavioral Neuroscience, 2020)
Do physical and psychosocial stressors interact to increase stress in ways not explainable by the stressors alone? A preliminary study compared participants’ stress response while subjected to a physical stressor (reduced or full physical load) and a predetermined social stressor (confronted by calm or aggressive behavior). Salivary cortisol samples measured endocrine stress. Heart rate variability and electrodermal activity measured autonomic stress. Perceived stress was measured via discomfort and stress state surveys. Participants with a heavier load reported increased distress and discomfort. Encountering an aggressive individual increased endocrine stress, distress levels, and perceived discomfort. Higher autonomic stress and discomfort were found in participants with heavier physical load and aggressive individuals. The results suggest a relationship where physical load increases the stressfulness of aggressive behavior in ways not explainable by the effects of the stressors alone. Future research is needed to confirm this investigation’s findings.